The asymptotic behavior of elementary symmetric functions on a probability distribution. (2001) - Kozyakin, V. S.; Pokrovskii, A. V.
Abstract : The problem on asymptotic of the value π ( m, n ) = m ! σ m ( p ( 1, n ), p ( 2, n ), …, p ( n, n ) ) is considered, where σ m ( x 1, x 2, …, x n ) is the m th elementary symmetric function of n variables. The result is interpreted in the context of nonequiprobable random mappings theory.